2022
DOI: 10.1007/s00270-022-03267-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New CT-Guided Robotic System for Percutaneous Needle Insertion for Thermal Ablation of Liver Tumors: A Prospective Pilot Study

Abstract: Purpose To assess the feasibility and safety of a robotic system for percutaneous needle insertion during thermal ablation of liver tumors. Materials and Methods This study analyzed the CT-guided percutaneous needle insertion using the EPIONE robotic device (Quantum Surgical, Montpellier, France) for radiofrequency or microwave liver ablation. The main criteria of the study were feasibility (possibility to perform the thermal ablation after needle insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…On average, each lesion required only 0.4 needle adjustments (±0.7), with only 29.2% of the lesions necessitating needle adjustment 37 . Feasibility was not compromised in case of lesions requiring substantial angulation and out‐of‐plane trajectories 37 . Complex targeting trajectories, including intercostal trajectories and steep trajectory angles, do not have any significant impact on the accuracy of targeting, as demonstrated in a study conducted by Tinguely et al 38 .…”
Section: Imaging Guidance and Margin Assessmentmentioning
confidence: 91%
See 2 more Smart Citations
“…On average, each lesion required only 0.4 needle adjustments (±0.7), with only 29.2% of the lesions necessitating needle adjustment 37 . Feasibility was not compromised in case of lesions requiring substantial angulation and out‐of‐plane trajectories 37 . Complex targeting trajectories, including intercostal trajectories and steep trajectory angles, do not have any significant impact on the accuracy of targeting, as demonstrated in a study conducted by Tinguely et al 38 .…”
Section: Imaging Guidance and Margin Assessmentmentioning
confidence: 91%
“…On average, each lesion required only 0.4 needle adjustments (AE0.7), with only 29.2% of the lesions necessitating needle adjustment. 37 Feasibility was not compromised in case of lesions requiring substantial angulation and out-of-plane trajectories. 37 Complex targeting trajectories, including intercostal trajectories and steep trajectory angles, do not have any significant impact on the accuracy of targeting, as demonstrated in a study conducted by Tinguely et al 38 In their experience, Lachenmayer et al 39 reported low average lateral and longitudinal errors (3.2 mm and 1.6 mm, respectively) without requiring supplementary techniques, like hydrodissection, to address anatomical difficulties and facilitate the placement of the ablation probe.…”
Section: Imaging Guidance and Margin Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPIONE robotic system (Quantum Surgical, Montpellier, France), both CE marked, and FDA cleared, is another robotic system used in CT-guided percutaneous needle insertion. The EPIONE robotic system has 6 DOF and is comprised of five components: the mobile arm (1) which has attached to it the needle guide (2), an infra-red camera (3) acting as the navigation cart, a workstation (4), and patient reference (5) which is adhesively attached to the patient’s skin and allows tracking of patient’s respiratory cycle [ 60 ]. This robotic system has been safely used in CT-guided percutaneous needle placement for targeting of previously implanted fiducials in the liver of ten swine [ 61 ].…”
Section: Robotic Non-vascular Systemsmentioning
confidence: 99%
“…All needle insertions successfully reached the target on the first attempt with no need for readjustment; however, there were two subcapsular haematomas which did not progress to retroperitoneal effusions [ 62 ]. In a recent prospective study, the EPIONE robotic system was used for robotic-assisted thermal ablation of liver tumours [ 60 ].…”
Section: Robotic Non-vascular Systemsmentioning
confidence: 99%